Induction of G(2) Arrest and Binding to Cyclophilin A Are Independent Phenotypes of Human Immunodeficiency Virus Type 1 Vpr - Ardon, Orly (American Society for Microbiology, 2006)
Cyclophilin A (CypA) is a member of a family of cellular proteins that share a peptidyl prolyl cis-trans isomerase (PPIase) activity. CypA was previously reported to be required for the biochemical stability and function (specifically, induction of G(2) arrest) of the human immunodeficiency virus type 1 (HIV-1) protein R (Vpr). In the present study, we examine the role of the Vpr-CypA interaction on Vpr-induced G(2) arrest. We find that Vpr coimmunoprecipitates with CypA and that this interaction is disrupted by substitution of proline-35 of Vpr as well as incubation with the CypA inhibitor cyclosporine A (CsA). Surprisingly, the presence of CypA or its binding to Vpr is dispensable for the ability of Vpr to induce G(2) arrest. Vpr expression in CypA(−/−) cells leads to induction of G(2) arrest in a manner that is indistinguishable from that in CypA(+) cells. CsA abolished CypA-Vpr binding but had no effect on induction of G(2) arrest or Vpr steady-state levels. In view of these results, we propose that the interaction with CypA is independent of the ability of Vpr to induce cell cycle arrest. The interaction between Vpr and CypA is intriguing, and further studies should examine its potential effects on other functions of Vpr.